Utilization of Power Plant and Agricultural Waste as A Cement Substitute on The Compressive Strength of Environmentally Friendly Concrete - purnomo, julyan; kamil, firmanilah (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
This study aims to assess the effect of using Fly Ash and Rice Husk Ash as cement substitutes in the manufacture of environmentally friendly concrete. Fly Ash, a waste from coal-fired power plants, and Rice Husk Ash, an agricultural waste, were used as partial cement substitutes in four concrete mix variations, viz: normal concrete without substitution (N), concrete with 20% Fly Ash (K), concrete with a combination of 10% Fly Ash and 10% Rice Husk Ash (L), and concrete with 20% Rice Husk Ash (M). The compressive strength test was conducted at the age of 7 days, 14 days, and 28 days. The results showed that concrete with 20% Fly Ash (K) produced the most optimal compressive strength, especially at longer concrete ages. Concrete with Rice Husk Ash substitution (M) and a combination of Fly Ash and Rice Husk Ash (L) showed lower compressive strength than normal concrete (N) and Fly Ash alone. Therefore, the use of Fly Ash at 20% gave the best compressive strength results among the variations tested. Keyword: Cement Substitution, Compressive Strength, Eco-friendly concrete, Fly Ash, Rice Husk Ash